2023
DOI: 10.3390/medicines10060033
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone-Associated Movement Disorder: A Literature Review

Abstract: Background: Fluoroquinolones (FQNs) are related to several central nervous system side effects. This review aims to evaluate the clinical-epidemiological profile, pathophysiological mechanisms, and management of FQNs-associated movement disorders (MDs). Methods: Two reviewers identified and assessed relevant reports in six databases without language restriction between 1988 and 2022. Results: A total of 45 reports containing 51 cases who developed MDs secondary to FQNs were reported. The MDs included 25 myoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
2
5
0
Order By: Relevance
“…Chau et al reported a patient with Creutzfeldt–Jakob disease-like syndrome induced by gabapentin toxicity, in which electrodiagnostic studies showed periodic sharp wave complexes [ 40 ]. A similar clinical manifestation with electrodiagnostic studies was already observed with amitriptyline [ 121 ] and fluoroquinolones [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Chau et al reported a patient with Creutzfeldt–Jakob disease-like syndrome induced by gabapentin toxicity, in which electrodiagnostic studies showed periodic sharp wave complexes [ 40 ]. A similar clinical manifestation with electrodiagnostic studies was already observed with amitriptyline [ 121 ] and fluoroquinolones [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
“…Movement disorder onset was defined as the time from the GBP start until the development of the movement disorder. Movement disorder recovery was defined as the time from the first management, which could be the GBP discontinuation, until the full recovery of the abnormal movement [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, myoclonus secondary to amantadine could be related to a serotonergic mechanism. A similar explanation has been hypothesized for other drug-induced myoclonus, such as lithium and fluoroquinolones [ 26 , 27 ]. Notably, these drugs share case presentation similarities regarding myoclonus and progressive cognitive impairment, known by some authors as Creutzfeldt–Jakob-like syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…Movement disorders, such as tremors or muscle spasms, have been reported in some cases, although these occurrences are rare [61]. The exact mechanism by which fluoroquinolones may contribute to movement disorders or neuromuscular symptoms is not fully understood [62]. It's important to note that the occurrence of movement disorders with fluoroquinolones is infrequent, and the overall benefit of these antibiotics in treating bacterial infections usually outweighs the risk of such side effects [63].…”
Section: Fluoroquinolonesmentioning
confidence: 99%